2009
DOI: 10.31729/jnma.289
|View full text |Cite
|
Sign up to set email alerts
|

Disease Management Programme for Diabetes Mellitus in Nepal

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 6 publications
1
4
0
Order By: Relevance
“…This study shows significant decrease in total serum calcium level in hypertensive patients than normotensive controls and the results are in close agreement with that of others who also found a significant decrease in serum calcium in patients with essential hypertension . 7,8 Though there are not enough study describing the relation of serum calcium and hypertension, but the findings of the present study are in agreement with that of Sudhakar, Sujhata, Babu, Padmanathi and Reddy. 28 Toyuz et al also reported reduced serum calcium level in hypertensive individuals.…”
Section: Totalsupporting
confidence: 91%
See 1 more Smart Citation
“…This study shows significant decrease in total serum calcium level in hypertensive patients than normotensive controls and the results are in close agreement with that of others who also found a significant decrease in serum calcium in patients with essential hypertension . 7,8 Though there are not enough study describing the relation of serum calcium and hypertension, but the findings of the present study are in agreement with that of Sudhakar, Sujhata, Babu, Padmanathi and Reddy. 28 Toyuz et al also reported reduced serum calcium level in hypertensive individuals.…”
Section: Totalsupporting
confidence: 91%
“…6 The percentage of diabetic patients has increased from 19.04% in 2002 to 25.9% in 2009 in Nepal. 7 .…”
Section: Introductionmentioning
confidence: 99%
“…Low- and middle-income countries bear a burden of about three quarters of diabetic population [ 1 ]. The prevalence of diabetes in Nepal is increasing [ 2 , 3 ] and is projected to reach 17.49% by 2020 [ 3 ]. Insulin is the indispensable component of the management of DM [ 4 ], and the proportions of patients using insulin vary from country to country [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Of all 52 macro-vascular complications CAD (n=30, 57.6%) were major, followed by Stroke (n=8, 15.38%), PVD (n= 8, 15.3%), CAD, PVD (n=3, 5.76%), and CAD, Stroke (n=3,5.76%). (Dulal and Karki, 2009;Juarez et al, 2006) Figure 4, shows different therapies used by type II diabetic patients in our study. Of all these therapies, dual therapy usage was mostly identi ied.…”
Section: Resultsmentioning
confidence: 98%